Relationship between manbibular angle fractures and mandibular third molars - An observational study - Sujeesh Koshy; Ravi Rajan; Krishnamoorthy Bonanthaya; Akhilesh Prathap; Anu Anna Wilson (Elsevier, 2021)
Mandibular fracture during lower third molar removal is an unusual and major complication though fracture of the tooth is common. Impacted mandibular third molar contributes to the weakness of the angle region of the mandible and increases the risk of its fracture. Symptoms can vary widely and treatment options range from prescription of a soft diet to surgical treatment by open reduction and internal fixation. Correlation between mesio-angular, horizontal, disto-angular and vertical tooth impaction with the incidence, displacement and management of fractures in the region of the mandibular third molar is being studied in this article.